2021
DOI: 10.3390/ijms222111810
|View full text |Cite
|
Sign up to set email alerts
|

Deacetylation of Transcription Factors in Carcinogenesis

Abstract: Reversible Nε-lysine acetylation/deacetylation is one of the most common post-translational modifications (PTM) of histones and non-histone proteins that is regulated by histone acetyltransferases (HATs) and histone deacetylases (HDACs). This epigenetic process is highly involved in carcinogenesis, affecting histone and non-histone proteins’ properties and their biological functions. Some of the transcription factors, including tumor suppressors and oncoproteins, undergo this modification altering different ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 117 publications
0
9
0
Order By: Relevance
“…Chromatin alteration by histone modification has epigenetic effects on various cellular processes such as DNA recombination, cell cycle progression, DNA repair, and apoptosis ( Chrun et al ., 2017 ). Histone deacetylases (HDACs) are known for their ability to remove acetyl groups at lysine residues in histone proteins, but recent several studies have demonstrated that they deacetylate both histones and non-histone proteins ( Mariadason, 2008 ; Ocker, 2010 ; Halasa et al ., 2021 ). The class III HDAC member sirtuin (SIRT), is a highly conserved group of seven proteins in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Chromatin alteration by histone modification has epigenetic effects on various cellular processes such as DNA recombination, cell cycle progression, DNA repair, and apoptosis ( Chrun et al ., 2017 ). Histone deacetylases (HDACs) are known for their ability to remove acetyl groups at lysine residues in histone proteins, but recent several studies have demonstrated that they deacetylate both histones and non-histone proteins ( Mariadason, 2008 ; Ocker, 2010 ; Halasa et al ., 2021 ). The class III HDAC member sirtuin (SIRT), is a highly conserved group of seven proteins in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Acetylation and deacetylation of lysine residues are reversibly regulated by acetyltransferase and deacetylase, which are implicated in tumour progression and metastasis. 48 To further unearth the enzymes related to the regulation of ACLY acetylation level, acetyltransferase (PCAF) and deacetylase (HDAC1 and SIRT2) were selected for further study, we found that ACLY had significant interaction with PCAF and SIRT2 in ESCC cells, but not HDAC1. However, because SIRT2 was significantly enriched in the protein complex, we used SIRT2 as Co-IP antibody for reverse verification by immunoprecipitation.…”
Section: Discussionmentioning
confidence: 99%
“…Histone acetylation and deacetylation are among the most common post-translational modifications. HDACs maintain a dynamic balance between acetylation and deacetylation ( 20 ), thereby regulating cell proliferation, apoptosis, metastasis, and cell cycle progression and affecting histone properties and their biological functions ( 21 , 22 ). Previous studies have demonstrated that HDAC5 is differentially expressed in tumor tissues.…”
Section: Discussionmentioning
confidence: 99%